Fibrillin: from domain structure to supramolecular assembly. - Handford, P; Downing, A; Reinhardt, D; Sakai, L (2000)
In the last 5 years, significant progress has been made in understanding the structure and function of all the major domains composing the fibrillins. A previous review [Meth. Enzymol. 245 (1994), 29] focused on the isolation of fibrillin monomers and fibrillin-containing polymers (microfibrils). In this article, information gained from recent studies which have further elucidated molecular structure and investigated effects of mutations on structural and functional properties will be summarized. In addition, studies of functional domains in fibrillins which may be important in assembling microfibrils will be discussed. Throughout this review, the authors have attempted to identify areas of research which have been controversial. In the conclusion, we raise important questions which remain unresolved.